Grief and Trauma in the Archives. Issue 4 (19th May 2023) - Regehr, Cheryl; Duff, Wendy; Aton, Henria; Sato, Christa
Abstract: Reporting on a qualitative study involving in-depth interviews, this paper seeks to elucidate the nature and factors associated with emotional responses in archivists working with records detailing human suffering and atrocity, and working with individuals in the community whose lives intersect with the archives. Results detail the impact of these exposures on archivists; and factors influencing emotional responses to traumatic exposures such as the nature of exposure, personal history and connections to the traumatic material, professional engagement and expectations, and the organizational context. Recommendations for mitigating the emotional toll of archival work arising from the data are presented.